Study of vertical load distribution in full-scale four-story masonry building - Andolfato, R. P. [UNESP]; Ramalho, M. A.; Corrêa, M. R.S.; Haach, V. G. (American Concrete Institute, 2014)
The vertical load distribution between the walls in a masonry building is a difficult issue in structural engineering. The absence of research regarding this subject results in using simple load distribution methods by the designers. This paper presents a study of the vertical load distribution between the walls in a full-scale four-story masonry building. Ninety blocks of a four-story building were instrumented with strain gauges and their behaviors were evaluated after an external loading was applied on some slabs. The distribution of the vertical loads in this building is also evaluated using a simple theoretical design model widely used in structural design practice. Experimental results exhibited vertical load redistribution between the walls and high influence of the flexure of slabs and walls on this distribution. Comparing experimental and theoretical results, there was similarity between the experimental and numerical results inside some wall groups, although the simple design model produced divergent stress values in the presence of significant flexural effects. © 2014, American Concrete Institute.
Keywords: Experimental analysis; Structural masonry; Theoretical design model; Vertical load distribution